Shape-Persistent (Pt-salphen)2 Phosphorescent Coordination Frameworks: Structural Insights and Selective Perturbations - Guo, Zhengqing; Yiu, Shek-Man; Chan, Michael C. W. (Chemistry : a European journal, 2013)
The development of molecular frameworks derived from binuclear platinum(II) aromatic Schiff base (salphen) complexes and their supramolecular chemistry have been undertaken. A series of axially rotating (Pt‐salphen)2 luminophores, tethered in a cofacial manner by a rigid linker (xanthene, 1; dibenzofuran, 2; biphenylene, 3), was synthesized in which the O(salphen) groups are potentially amenable for guest‐binding. The molecular structures of 1 and 3 have been determined by X‐ray crystallography, revealing intra‐ and intermolecular π‐stacking interactions, as well as contrasting syn (1) and anti (3) configurations, for the (Pt‐salphen)2 moiety. All complexes are luminescent in solution at room temperature. Their photophysical and solvatochromic properties have been examined, and the emissions are assigned to mixed triplet O(p)/Pt(d)→π*(diimine) excited states. The red‐shifted fluid emissions and lower quantum yields of 1 and 3, relative to 2, are ascribed to enhanced intramolecular π‐stacking interactions. Photophysical changes and selective responses to metal ions (particularly Pb2+) have been investigated by using various spectroscopic methods and DFT calculations, and through comparative studies with control complexes. A plausible binding mechanism is proposed based on occupation of the O(salphen)‐binding cavity, which induces perturbation of intramolecular π–π interactions, and hence the self‐quenching and emission properties, of the (Pt‐salphen)2 unit. To π or not to π? The ratiometric phosphorescent ion‐selective responses of axially rotating binuclear assemblies have been investigated by using X‐ray crystallography, DFT calculations, and various spectroscopic techniques to provide an insight into the binding mechanism (see figure). These results may carry important implications for stimuli‐responsive luminescent host complexes that engage in intramolecular interactions.